(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
Aim.: Τo investigate the Mobbing phenomenon in the workplace, Material And Methods: We investigated the Mobbing by reviewing previous international research over mobbing. The research material was accumulated after thoroughly examining former studies and reviewing the existing literature, as it was found in the bibliography, data bases, academic libraries, academic journals and the internet. Results: Through the research we tried to define this phenomenon and at the same time to study it in the workplace. Finally, we conducted a literature review from previous research in order to investigate this phenomenon and its factors. Conclusions: The current study has concluded that mobbing sadly negatively affects the recipient by creating both direct and indirect effects on various aspects of his daily life, one of which is the workplace.